A Debreceni Kossuth Lajos Tudományegyetem archontológiája 1950–1990. VII. rész - Mudrák, József (Gerundium, 2017)
The Archontology of Lajos Kossuth University of Arts and Sciences (1950–1990), Part Vii: Institute of Biology. The Archontology of Kossuth University for the School of Arts, the School of Sciences, and for the So-Called „Central Units” between January 1, 1950, and December 31, 1990, was assembled on the basis of the personal cards and personal files archived in the Personnel Department of the Rector’s Office. As the 1950s has not furnished sufficiently with documents data was supplemented by the annually arrangedmaterial of the Personnel Office. Even so, however, the existing material fails to be complete by making impossible to realize the archontology with perfect accuracy. Part VII presents the complete list of the Institute of Biology from institute head to janitor.